A reforma agrária como uma política pública de desenvolvimento ou política social? Uma análise a partir dos assentamentos rurais Tereza do Cedro e Dandara no município de Uberaba/MG - Masson, Gabriela Abrahão [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
According to Barbosa (2012), Brazil has one of the biggest land concentration in the world. Only 0,8% of land owners have possession of 31,6% of arable lands. It is estimated that promoting a land reform, which would raise the decentralisation of land structure in Brazil, would directly benefit 2,5 million of landless families. Land reform, thus, as a public policy of development, together with either agricultural and social policies, could trigger a rural development process in Brazil, sustained not only by an agricultural development. On the other hand, it is known that the social, political, economical, therefore historical options made by the earlier Brazilian governments on land reform now lead to a “non-land reform”, according to Oliveira (2011). Thereby, much more than a dispossession policy is expected for solving the social inequality that follows the rise of the country, with public policies that may contribute and enhance the sojourn of settled people in the rural settlements. In this thesis, we aim to question, discuss and think over the land reform ongoing in Uberaba, and if it can be whether characterized as a public policy of development or becomes an increasingly selective, focused and compensatory social policy. Therefore, a bibliographic, documental research was made, which enabled a theoretical practical essential improvement for the reflective process of the information obtained on field research and on participant observation. The following settled people of land reform who live in the rural settlements were interviewed by semi-structured interviews: Political leadership, Uberaba’s secretary of agriculture, livestock, fishing and apiculture and the state superintendent of Incra of Minas Gerais. The data analysis were based on qualitative methodology and the materialistic historical dialectic method of apprehension of reality enabled consecutive approaches to the unique situation studied. It allowed us to seize that the constitution of the rural settlements studied has many contradictions that enforced numerous challenges to the settled people current routine. Thus, the ongoing land reform in the settlements is still a procedure that is in force and is affected by structural elements of Brazilian reality, which daily invalidate the land reform process as a public policy of development. However, the tone of class struggle for peasants and landless workers in these settlements is the promise for possible better conditions of life and work.

A concentração fundiária no Brasil segundo Barbosa (2012) é uma das maiores do planeta. Apenas 0,8% dos proprietários rurais ocupam 31,6 % das terras agricultáveis. Estima-se que a realização da reforma agrária, promovendo a desconcentração da estrutura fundiária no Brasil, beneficiaria diretamente 2,5 milhões de famílias sem-terra. Neste contexto a reforma agrária, enquanto política pública de desenvolvimento, juntamente com as políticas agrícolas e sociais poderia desencadear em nosso território um processo de desenvolvimento rural sustentado não apenas de desenvolvimento agrícola. No entanto, sabemos que as opções sociais, políticas, econômicas, portanto históricas que perpassaram os governos brasileiros, em torno da reforma agrária resultam na atualidade em uma “não reforma agrária”, nos termos de Oliveira (2011). Assim, para que se possa dirimir a desigualdade social engendrada no país desde sua constituição pressupõe-se muito mais que um a política de desapropriação, mas sim políticas públicas que contribuam e fortaleçam para permanência dos assentados e assentadas nos assentamentos rurais do Brasil. Nesta tese visamos problematizar, discutir e refletir se a reforma agrária em curso em Uberaba se caracteriza enquanto política pública de desenvolvimento ou se torna cada vez mais uma política social seletiva, focalizada e compensatória. Para tanto, realizamos pesquisa bibliográfica, documental que possibilitaram aprofundamento teórico prático essencial para o processo reflexivo das informações obtidas na pesquisa de campo e na observação participante. Entrevistamos os assentados e as assentadas da reforma agrária que residem nos assentamentos rurais em questão, Liderança política, o Secretário de Agricultura, Pecuária, Pesca e Apicultura de Uberaba e o Superintendente Estadual do Incra de Minas Gerais, por meio da entrevista semiestruturada. A análise dos dados foi pautada na metodologia qualitativa e o método materialista histórico dialético de apreensão da realidade possibilitou sucessivas aproximações à particularidade estudada. Podemos apreender que a constituição dos assentamentos rurais estudados possui muitas contradições que impuseram muitos desafios ao cotidiano dos assentados e assentadas na atualidade. A Reforma Agrária em curso nestes assentamentos ainda se constituí um processo em construção perpassado por elementos estruturais da realidade brasileira que diariamente inviabilizam a reforma agrária enquanto política pública de desenvolvimento neste território. No entanto, a tônica da luta de classes dos camponeses, trabalhadores e trabalhadoras sem-terra nestes assentamentos é o horizonte que pode se traduzir em melhores condições de vida e trabalho.

La concentración fundiaria en Brasil según Barbosa (2012) es una de las mayores del planeta. Apenas 0,8% de los propietarios rurales ocupan 31,6% de las tierras agricultables. Es estimado que la realización de la reforma agraria, promoviendo la desconcentración de la estructura fundiaria en Brasil, beneficiaría directamente 2,5 millones de familias sin tierra. En este contextos la reforma agraria, mientras política pública de desarrollo, junto a las políticas agrícolas y sociales podría desencadenar en nuestro territorio un proceso de desarrollo rural sostenido no apenas de desarrollo agrícola. Entretanto, sabemos que las opciones sociales, políticas, económicas, por lo tanto históricas que atraviese los gobiernos brasileños, en torno de la reforma agraria resultan en la actualidad en una “no reforma agraria”, en las palabras de Oliveira (2011). Así, para que se pueda obstruir la desigualdad social engendrada en el país desde su constitución se presupone no solo una política de desapropiación, pero mucho más: políticas públicas que contribuyan y fortalezcan la permanencia de los asentados y asentadas en los asentamientos rurales de Brasil. En esta tesis visamos problematizar, discutir y reflectar si la reforma agraria en curso en Uberaba se caracteriza mientras la política pública de desarrollo o se torna cada vez más una política social selectiva, focalizada y compensatoria. De esta forma, realizamos una pesquisa bibliografía, documental que posibilitó profundización teórica practica esencial para el proceso reflexivo de las informaciones obtenidas en la pesquisa de campo y en la observación participante. Entrevistamos los asentados y las asentadas de la reforma agraria que residen en los asentamientos rurales en cuestión, Liderazgo político, el Secretario de Agricultura, Pecuaria, Pesca y Apicultura de Uberaba y el Superintendente Estadual do Incra de Minas Gerais, por intermedio de la entrevista semiestructurada. El análisis de los dados fue pautada en la metodología cualitativa y el método materialista histórico dialectico de aprensión de la realidad posibilitó sucesivas aproximaciones a la particularidad estudiada. Podemos aprehender que la constitución de los asentamientos rurales estudiados poseen muchas contradicciones que impusieron muchos desafíos en el cuotidiano de los asentados y asentadas en la actualidad. La Reforma Agraria en curso en estos asentamientos aún se constituye un proceso en construcción atravesado por elementos estructurales de la realidad brasileña que diariamente inviabiliza la reforma agraria como política pública de desarrollo en el territorio. Entretanto, en punto principal de la lucha de clases de los campaneases, trabajadores y trabajadoras sin tierra en estos asentamientos es el horizonte que se puede traducir en mejores condiciones de vida y trabajo.
La reforma agraria como una política pública de desarrollo o política social? Un análisis a partir de los asentamientos rurales Tereza do Cedro y Dandara de Uberaba/MG
Is land reform a public policy of development or a social policy? An analysis based on the rural settlements Tereza do Cedro and Dandara of Uberaba/MG
Keywords: Questão agrária; Reforma agrária; Assentamentos rurais; Políticas públicas; Cuestión agraria; Asentamientos rurales; Agrarian issues; Land reform; Rural settlements; Public policy